Jewish Roots A Foundation of Biblical Theology. - Juster, Dan. (Shippensburg : Destiny Image Messianic, 2011)
Messianic Judaism is a grass roots movement--a movement among Jewish and non-Jewish followers of Jesus of Nazareth who recognize and identify with their Jewishness. As a pulsating grass roots movement, Messianic Judaism exhibits the power and excitement of significant new discoveries.Topical chapters in Jewish Roots discuss the following: The Biblical Meaning of Israel Israel's Call and the New Testament Messianic Judaism--Difficult Passages History of Judaism and Christianity The Faith and Life of Messianic Jews Paul, Israel, and the Law Messianic Jewish Practice.
Appendix I: The 613 LawsAppendix II: Major Writings Supporting Positions Taken; Appendix III: Fuller Theological Seminary News Release; Appendix IV: When Is Ritual Idolatry?; Notes; A Selected Bibliography
Description based upon print version of record.
Keywords: Jewish Christians; RELIGION / Christianity / Denominations; Electronic books